The Impact of Landfill Leachate Jatibarang Towards the Diversity and Abundance of Plankton in the Waters of Kreo River Semarang City - Astin Kurniawati; Ary Susatyo Nugroho; Fibria Kaswinarni (Universitas Sebelas Maret, 2015)
Plankton is the important organisms in aquatic ecosystems. Kreo river subjacent landfill leachate tank Jatibarang interchangeable physicochemical changes by leachate contaminants which enter the river due to leakage of leachate tank. The will impact on the diversity and abundance of plankton. The aims of this study is apperceiving Jatibarang leachate influence the diversity and abundance of plankton in Kreo River. The study was conducted from April to May 2015. Plankton samples taken by purposive sampling using a plankton net which 25 number with a mesh size of 40 µm. Sampling was conducted plankton with four stations of three sampling each points of stations and physicochemical measurements that include temperature, brightness, pH, COD, and BOD. That are contaminated leachate of II stations with an index of H’ value 1.40 and abudance 75 ind/l and the stations III with index H’ value 1,53 and abudance 95 ind/l. The location padding contaiminatef leachate that the stations I had an index value H’ 195 and abudance values 191 ind/l and stations which has undergone restoration gas an index value H’ 2,07 and abudance 207 ind/l. From the results shows that Jatibarang landfill leachate that entered the Kreo River affect the physicochemichal conditions of water allows for lowering the diversity and abudance of plankton Keywords: leachate, landfill Jatibarang, plankton, Kreo river